Study on the Pattern of wintering mallard using the Wild-Tracker (WT-300) in Korea - Sang-Min Jung; Park Hong Sik; Wooseog Jeong; Yong-Myong Kang; Hachung Yoon; Tehan Kang; Young-Un Shin; Si-Wan Lee; Hong-Shik Oh (한국조류학회지, 2017)
The mallard is the main wintering bird in Korea, also known as a main agent of avian virus. This study was carried out for understanding the mallard’s moving distance in winter and moving pattern from surround Mankyeong river of Korea. In 2015, 21 mallards were caught by Cannon-net, and attached the wild-tracker (WT-300, GPS-Mobile phone based telemetry, KoEco). Mallard’s moving distance between each coordinates that were transmitted by time were calculated. Monthly movement of mallards showed increasing in maximum moving distance from early November to early December, and showed distributing from the existing wintering place in December. After January, in the middle of wintering, the mallards tended to move wintering place without its big movement. Average moving distance by time in each day was 0.9 km, farthest movement was during 6:30-18:30 and after that during 6:30-8:30. Time spent in night foraging area was twice than in day foraging area. Consequently, the domestic mallards tend to distribute in December month in wintering period, after that they move short distance in the wintering area. Continuous studies on moving pattern of these species required for their protection, habitat management, and planning to the preventive measures against the high pathogenic avian influenza. KCI Citation Count: 1